Correction to: Anonymous shell companies: A global audit study and field experiment in 176 countries. Issue 2 (February 2018) - Allred, Brent; Findley, Michael; Nielson, Daniel; Sharman, J
Abstract Owing to a production error, a number of values were omitted in Table 1 of this article. A corrected version of this table is provided here. The corrected values are italicized.